2009
DOI: 10.1111/j.1556-4029.2009.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Clothing and Wrapping on Carcass Decomposition and Arthropod Succession During the Warmer Seasons in Central South Africa*

Abstract: The influence of clothing and wrapping on carcass decomposition and arthropod succession was investigated to provide data to enable estimated postmortem interval in homicide investigations. Six pig carcasses, Sus scrofa, were divided into three sample groups, each with a clothed carcass wrapped and a carcass wrapped with no clothes. Two more carcasses, one with no clothes or wrapping, the other with clothes and no wrapping were used as controls. The clothed or wrapped carcasses had larger visible maggot masses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
68
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 29 publications
11
68
0
Order By: Relevance
“…The putrefaction process will alter the surroundings and eventually promote the microorganism activity producing the decomposition odour that consequently attracting the dipteran to accelerate the process. Physical barrier wrapping factor and cementing factor might have played an important role to prevent the dipteran activity [25,37]. Even though time taken were not signi icantly different for ground exposed and wrapped control carcasses to reach irst sign of skeletonised stage, it was signi icant under freshwater as wrapping factor delay the decomposition by 2 times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The putrefaction process will alter the surroundings and eventually promote the microorganism activity producing the decomposition odour that consequently attracting the dipteran to accelerate the process. Physical barrier wrapping factor and cementing factor might have played an important role to prevent the dipteran activity [25,37]. Even though time taken were not signi icantly different for ground exposed and wrapped control carcasses to reach irst sign of skeletonised stage, it was signi icant under freshwater as wrapping factor delay the decomposition by 2 times.…”
Section: Discussionmentioning
confidence: 99%
“…Six pig carcasses were divided into three sample groups, each with a clothed carcass wrapped and a carcass wrapped with no clothes. The results showed that clothed or wrapped carcasses had larger visible maggot masses, which moved more freely and these carcasses took longer to dry out [18]. The effect of clothing on carcass decomposition and patterns of insect succession onto remains were also investigated during autumn in Western Australia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…No animals were hence subjected to euthanasia for the purposes of the study. Pigs were considered a reliable analogical model due to similarities with the human body in terms of weight, fat-to-muscle ratio and hair coverage [7,[17][18][19][20]. The mean weight chosen was about 80 kg, similar to that of an average adult male human body.…”
Section: Targets and Test Pitsmentioning
confidence: 99%
“…It is necessary to study the entomofauna found at the scene and on the deceased body [2][3][4]. The insects are organisms whose duration of development is influenced by environmental factors and this must be taken into account for the PMI estimation.…”
Section: Introductionmentioning
confidence: 99%